Personalized development of human organs using 3D printing technology. (February 2016) - Radenkovic, Dina; Solouk, Atefeh; Seifalian, Alexander
Abstract: 3D printing is a technique of fabricating physical models from a 3D volumetric digital image. The image is sliced and printed using a specific material into thin layers, and successive layering of the material produces a 3D model. It has already been used for printing surgical models for preoperative planning and in constructing personalized prostheses for patients. The ultimate goal is to achieve the development of functional human organs and tissues, to overcome limitations of organ transplantation created by the lack of organ donors and life-long immunosuppression. We hypothesized a precision medicine approach to human organ fabrication using 3D printed technology, in which the digital volumetric data would be collected by imaging of a patient, i.e. CT or MRI images followed by mathematical modeling to create a digital 3D image. Then a suitable biocompatible material, with an optimal resolution for cells seeding and maintenance of cell viability during the printing process, would be printed with a compatible printer type and finally implanted into the patient. Life-saving operations with 3D printed implants were already performed in patients. However, several issues need to be addressed before translational application of 3D printing into clinical medicine. These are vascularization, innervation, and financial cost of 3D printing and safety of biomaterials used for the construct.